Advancing implementation of the AfCFTA Protocol on Digital Trade in Nigeria - Prachi Agarwal; Sand Kalu Mba; Alberto Lemma (ODI, 2024)
The African Continental Free Trade Area (AfCFTA) is a milestone in the continent's economic integration and development. The AfCFTA Protocol on Digital Trade offers a transformative opportunity for Nigeria, Africa's leading economy and tech hub, to harness its burgeoning digital economy for sustainable growth and regional integration. This report explores the potential impact of adopting this protocol, analysing its effects on Nigeria's economic growth, digital infrastructure, trade costs and digital inclusivity. Through extensive research and modelling, the report projects substantial GDP growth projections, increased employment opportunities and a considerable boost in exports, all achievable through targeted policy interventions. While the Protocol presents significant opportunities for Nigeria, challenges such as infrastructure limitations, cybersecurity threats and regulatory alignment must be addressed for the country to fully harness the benefits of digital trade under the AfCFTA. The report provides actionable policy recommendations to navigate these challenges, including developing a comprehensive digital trade policy, fostering inter-ministerial collaboration, reforming the domestic regulatory environment and establishing national digital laws. It also emphasises the importance of adopting international standards, enhancing the innovation environment and promoting digital inclusivity, particularly for women and youth. By prioritising these reforms, Nigeria can not only consolidate its position as a leader in Africa's digital economy but also contribute to the continent's broader economic integration and development under the AfCFTA.
Keywords: 330; Digital; Economic transformation; Economic growth; Nigeria; Africa; Trade & investment